Linking the Developmental and Degenerative Theories of Schizophrenia: Association Between Infant Development and Adult Cognitive Decline - Kobayashi, H; Isohanni, M; Jaaskelainen, E; Miettunen, J; Veijola, J; Haapea, M; Jarvelin, M-R; Jones, PB; Murray, GK (Schizophrenia Bulletin, 2014)
Neurodevelopmental and neurodegenerative theories may be viewed as incompatible accounts that compete to explain the pathogenesis of schizophrenia. However, it is possible that neurodevelopmental and neurodegenerative processes could both reflect common underlying causal mechanisms. We hypothesized that cognitive dysfunction would gradually deteriorate over time in schizophrenia and the degree of this deterioration in adulthood would be predicted by an infant measure of neurodevelopment. We aimed to examine the association between age of learning to stand in infancy and deterioration of cognitive function in adulthood. Participants were nonpsychotic control subjects (n = 76) and participants with schizophrenia (n = 36) drawn from the Northern Finland 1966 Birth Cohort study. The schizophrenia group showed greater deterioration in abstraction with memory than controls, but there were no differences between schizophrenia and controls in rate of change of other cognitive measures. Age of learning to stand in infancy significantly inversely predicted later deterioration of abstraction with memory in adult schizophrenia (later infant development linked to greater subsequent cognitive deterioration during adulthood), possibly suggesting a link between abnormal neurodevelopmental and neurodegenerative processes in schizophrenia.